If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3 + -1x) = 4(x + -3) (3 * 5 + -1x * 5) = 4(x + -3) (15 + -5x) = 4(x + -3) Reorder the terms: 15 + -5x = 4(-3 + x) 15 + -5x = (-3 * 4 + x * 4) 15 + -5x = (-12 + 4x) Solving 15 + -5x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + -5x + -4x = -12 + 4x + -4x Combine like terms: -5x + -4x = -9x 15 + -9x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + -9x = -12 + 0 15 + -9x = -12 Add '-15' to each side of the equation. 15 + -15 + -9x = -12 + -15 Combine like terms: 15 + -15 = 0 0 + -9x = -12 + -15 -9x = -12 + -15 Combine like terms: -12 + -15 = -27 -9x = -27 Divide each side by '-9'. x = 3 Simplifying x = 3
| (3z+5)+(7z-5)+90=180 | | 7+4(2+3x)=-15 | | 90-4x=15x-5 | | 5n+5.23=109.73 | | 5y-2+8y=31 | | (3z+1)+(2z-6)+90=180 | | 7(a-8)+33=3(a-5) | | 20=y-9 | | 7x+3-5x+8+4x-1= | | z+8=-20 | | (3z+1)+(2z-6)=180 | | N/9+10.36=25.36 | | 6(x-3)=4(x-4)+2(x-1) | | N/6+3=12 | | 2X^2+5X=2X+9 | | 6(x+5)=7x+30 | | 8x+37=8x+13 | | (6z-12)+(5z+16)=180 | | z^2+4z+4+2i=0 | | 1+3(x-5)=7+x | | 0.6a=6 | | (6z-12)+(5z+16)=90 | | 7(x+7)=8x+40 | | 7x+3-5x+84x-1= | | 0.625=0.5r | | (6z+12)+(5z+16)=90 | | N^2-4N-5=0 | | W-4.58=1.78 | | 3/4(t-2)-2/5(2t-3)=3/5 | | 10x-4=8x+1 | | .03n=0.2 | | 4x-1+6x+11=120 |